2012
DOI: 10.1007/s10552-012-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation, MTHFR and MTRR polymorphisms, and the risk of childhood leukemia: the ESCALE study (SFCE)

Abstract: The study findings support the hypothesis that maternal folic acid supplementation may reduce the risk of childhood AL. The findings also suggest that the genotype homozygous for any of the MTHFR variants and carrying both MTRR variants could be a risk factor for AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 58 publications
10
60
1
2
Order By: Relevance
“…Consistent with our findings for the child's MTRR 66A>G genotype, four of seven previous studies reported at least some evidence of a protective effect of the mutant allele (24,(26)(27)(28). In addition, a meta-analysis of three studies assessing this polymorphism (26-28) reported summary ORs for AG and GG of 0.76 (95% CI, 0.60-0.96) and 0.67 (95% CI, 0.52-0.88), respectively (13).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our findings for the child's MTRR 66A>G genotype, four of seven previous studies reported at least some evidence of a protective effect of the mutant allele (24,(26)(27)(28). In addition, a meta-analysis of three studies assessing this polymorphism (26-28) reported summary ORs for AG and GG of 0.76 (95% CI, 0.60-0.96) and 0.67 (95% CI, 0.52-0.88), respectively (13).…”
Section: Discussionsupporting
confidence: 92%
“…For the MTHFR genotypes, however, a number of previous studies suggested that 677C>T may be protective, but that 1298A>C was not associated with risk (14, 15). We did not find evidence of a reduced risk with either polymorphism overall, similar to two recent studies (22,24).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations